SLOfit ali športnovzgojni karton skozi zgodovinsko perspektivo - Kovač, Marjeta (Šport (Ljubljana), 2017)
The article presents the historical development of the study of physical and motor development of children and adolescents in Slovenia, especially the establishment and formulation of the national central information system "Sports Educational Chart", which the authors first named Physical Educational Chart and later Sports Educational Chart, whereas today the name "SLOfit system" has increasingly been gaining ground. This term is also applied when we present our database abroad. The system was developed between 1969 and 1989, whereas in 1996 the data collection became one of the compulsory databases that every Slovenian school has been maintaining in compliance with the school legislation. The study and design of a battery of measurement tasks for assessing the indicators of physical and motor development are presented from the historical perspective, along with the changes in the purpose of the database and the legislation concerning the integration of the Sports Educational Chart in the school system, the most important development landmarks from 1969 to the present day as well as application of data in national and international studies.
Keywords: adolescents; children; gibalni razvoj; historical development; javno zdravje; mladina; motor development; nacionalna zbirka; namen; national database; otroci; physical activity; physical development; politics; politika; public health; purpose; SLOfit; sport; šport; športna vzgoja; športnovzgojni karton; telesna dejavnost; telesni razvoj; zgodovinski razvoj